1989
DOI: 10.1111/j.1365-2125.1989.tb05373.x
|View full text |Cite
|
Sign up to set email alerts
|

A controlled evaluation of a homoeopathic preparation in the treatment of influenza‐like syndromes.

Abstract: 1. A controlled clinical trial was conducted to assess the effectiveness of a homoeopathic preparation in the treatment of influenza‐like syndromes. 2. 237 cases received the test drug and 241 were assigned to placebo. Patients recorded their rectal temperature twice a day, and the presence or absence of five cardinal symptoms (headache, stiffness, lumbar and articular pain, shivers) along with cough, coryza and fatigue. 3. Recovery was defined as a rectal temperature less than 37.5 degrees C and complete reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 10 publications
3
58
0
1
Order By: Relevance
“…These results are in line with studies in the literature that demonstrate the effectiveness of homeopathic medicine compared with allopathy or placebo in patients with acute 20,[27][28][29][30] or chronic 31−35 diseases of the ear, sinuses, and upper airways. Patients who used homeopathic medicines in our study did not have a reduced chance of recovery at 3 days and presented with improved symptoms without suffering more complications or side effects than patients taking allopathic medicines only.…”
Section: ■■ Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are in line with studies in the literature that demonstrate the effectiveness of homeopathic medicine compared with allopathy or placebo in patients with acute 20,[27][28][29][30] or chronic 31−35 diseases of the ear, sinuses, and upper airways. Patients who used homeopathic medicines in our study did not have a reduced chance of recovery at 3 days and presented with improved symptoms without suffering more complications or side effects than patients taking allopathic medicines only.…”
Section: ■■ Discussionsupporting
confidence: 81%
“…Two previous studies reported that Anas barbariae 200C (Oscillococcinum) was effective in ILI and resulted in a significantly greater decrease in symptoms after 48 hours of treatment and a shorter illness duration compared with placebo, with a significantly greater proportion of patients considering that homeopathy had been effective. 20,27 No data on efficacy are available in the literature for homeopathic combinations of several stocks (L52 or STODAL), but in a comparative study of homeopathy versus conventional treatment in the primary care setting, Haidvogl et al (2007) reported that homeopathic treatment for acute respiratory and ear complaints was not inferior to conventional treatment. 29 A total of 62 different homeopathic medicines were prescribed, with Belladonna (13.3%) and Pulsatilla (10.6%) the most frequently given to children and Hepar sulphuris (9.7%) and Belladonna (8.3%) the most frequent for adults.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…Homeopathy as cited by WHO has been used successfully for the prevention and treatment of a number of infectious diseases, including influenza and diarrhea [8][9][10][11] and also have found to be a major contributor to attenuate the symptoms of dengue fever. To the best of our knowledge, there have been no previous studies that evaluated the efficacy of homeopathy medications in dengue fever in terms of their effect on clinical hematological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The only disease to date for which there has been multiple large-scale, double-blinded clinical studies conducted by independent researchers using homeopathic medications is influenza, a common viral condition (Casanova and Gerard, 1992;Ferley et al, 1989;Papp et al, 1998). These studies treated 487,300, and 372 patients, and each yielded statistically significant results.…”
Section: Research On Viral Infections and Diseases Of The Immune Systemmentioning
confidence: 99%